New Anti - Dumping Theory of Cost Averages: A Solution to the Anti - Dumping War - Kaushik, K. R.; Sharma, Sharat (Indian Journal of Finance, 2015)
The basic objective of the WTO anti - dumping agreement is to restrict "dumping" that leads to material injury to the domestic industry in the host country. Unbridled and protectionist use of anti - dumping duties has impacted the international trade negatively in the form of trade loss, trade restriction, trade deviation retaliations, hardship to the consumers on account of choice of variety, and price of the products. While WTO in general advocates for free trade, the concept of dumping appears contrary to the very purpose for which WTO was created. However, free trade should be fair trade also, and therefore, the concept of free trade should not lead to a situation where an established industry in the importing country collapses and dumping by foreign exporters results into monopolization of markets in due course. Certain loopholes in the GATT/WTO agreement on anti - dumping are : No definition of like products, low prices charged for sales in the domestic markets are normally ignored to boost up the domestic sales price, investigating authorities typically follow accounting practices of the importing country, confusion of date of sale and exchange rates, fixation of dumping margin and circumvention lead to controversial practices and methodologies. Particularly, the "Zeroing Methodology" used by the industrialized countries in calculation of the dumping margin has further aggravated the situation. The fact remains that the anti - dumping actions are increasing substantially. During 1.1.1995 to 30.6. 2014, total 4627 anti - dumping investigations were made throughout the world, and 2966 antidumping actions are in force. Base metals&articles (1328 cases) and chemical and allied products (928 cases) are the most targeted sectors facing anti - dumping actions worldwide. India has imposed 529 measures and is also facing 104 anti - dumping measures on its products. The U.S. has imposed 326 measures and is facing 157 anti - dumping measures. Out of the 106 disputes pending in DSB on anti - dumping, the U.S. is involved in 57 cases, and India is involved in 17 cases. Trading countries are almost engaged in a trade war and anti - dumping measures are being challenged at the WTO frequently, but no solution has been found so far to restrict the anti - dumping war. The present paper presented a workable solution in the form of a proposed theory - The New Anti - Dumping Theory of Cost Averages or NATOCA.